A influência do jateamento na cimentação de bandas ortodônticas - Weissheimer, Felipe; Marchioro, Ernani Menezes [UNESP]; Dolci, Gabriel Schmidt; Spohr, Ana Maria; Hahn, Luciane [UNESP] (Dental Press Editora, 2006)
AIM: to compare the shear-peel bond strength of five orthodontic cements: a conventional glass ionomer cement (Ketac Cem), two resin-modified glass ionomer cements (3M Multicure Glass Ionomer and Fuji Ortho LC) and two polyacid-modified composite resin cement (Ultra Band-Lok and Transbond Plus). METHODS: cements were placed in a 3mm diameter mold at bonding interface and bonded to 6 x 6mm standard and sandblasted stainless steel band specimens mounted to acrylic blocks. Specimens were stored at 37ºC and 100% relative humidity for 24 hours and debonded in tension on a testing machine at 0.05cm/minutes. Data were analyzed by one-way analysis of variance (ANOVA) followed by a Tukey multiple comparison procedure in the same surface treatment groups (sandblasted or non-sandblasted) and by paired t-tests in different surface treatment groups (sandblasted and non-sandblasted) (p=0.01). RESULTS: Ultra Band-Lok demonstrated significant greater shear-peel bond strength (p<0.01) in the non-sandblasted groups, and no statistically significant differences were noted between others cements. In the sandblasted groups, resin-modified glass ionomer cements demonstrated the highest mean bond strength (p<0.01), and 3M Multicure Glass Ionomer showed a greater shear-peel bond strength (p<0.01) than Ketac Cem and Fuji Ortho LC. CONCLUSION: sandblasting increased shear-peel bond strength in all tested groups (p<0.01).

OBJETIVO: comparar a resistência ao cisalhamento de cinco materiais utilizados na cimentação de bandas ortodônticas: um cimento de ionômero de vidro convencional (Ketac Cem), dois cimentos de ionômero de vidro modificados por resina (3M Multicure Glass Ionomer Cement e Fuji Ortho LC) e duas resinas compostas modificadas por poliácidos (Ultra Band-Lok e Transbond Plus). METODOLOGIA: sobre a superfície de um segmento de banda (6 x 6mm) foi posicionada uma matriz com um orifício de 3mm de diâmetro na qual foi inserido o material para cimentação. Metade da amostra foi jateada com partículas de óxido de alumínio. Os corpos-de-prova foram armazenados a 37ºC por 24 horas em umidade relativa de 100% e submetidos ao teste de cisalhamento a uma velocidade de 0,5mm/min. Utilizou-se ANOVA e o teste de comparações múltiplas de Tukey para comparar os grupos em cada tipo de superfície estudada (com ou sem jateamento), e o teste t Student para amostras pareadas para a comparação dos grupos jateados e não-jateados (p=0,01). RESULTADOS: nos grupos não-jateados, Ultra Band-Lok apresentou uma resistência de união significativamente maior (p<0,01) que a obtida pelos outros materiais, os quais não apresentaram diferença significante entre si. Após o jateamento, as resinas compostas modificadas por poliácidos apresentaram uma resistência de união significativamente maior (p<0,01) que a obtida pelos demais cimentos, sendo que 3M Multicure Glass Ionomer apresentou um valor de união superior (p<0,01) ao obtido pelo Ketac Cem e Fuji Ortho LC. CONCLUSÃO: o jateamento aumentou significativamente (p<0,01) a resistência de união em todos os grupos.
The effect of sandblasting in band cementation
Keywords: Orthodontic banding; Sandblasting; Shear-peel bond strength; Cimentação de bandas; Jateamento; Resistência ao cisalhamento